FLOYD-warshall in Scheduling Open Networks. (2016) - Vattai, Zoltán A.
Abstract: After introducing main principles of transitive closure of graphs the paper discusses application of a modified Floyd-Warshall algorithm to calculate network time models of projects with no concern on whether the graph has one or more starting and/or ending node(s), whether it includes logical loop(s) or not, whether it is a connected model or not, whether it necessitates positive (lower bound) or negative (upper bound) or multiple restrictions amongst the time data of the project elements or not – that is: to schedule open networks. The method may contribute to generalization of network time models especially when considered in multi-project management context.